INDIVIDUALS WITH SPECIAL NEEDS IN ISLAMIC AND PSYCHOLOGICAL VIEWS AS WELL AS INCLUSIVE EDUCATION AS EDUCATIONAL EQUALITY - Rabbi, Mim Fadhli; Ramli, M. (STKIP PGRI Situbondo, 2025)
This study explores individuals with special needs (ISN) through the integration of psychological and Islamic perspectives. Using a library research approach, the study analyzes various literature to understand the multidimensional aspects of ISN. The Islamic perspective emphasizes that a person’s dignity is determined by piety, not physical or mental conditions. Psychology provides insights into the importance of inclusive approaches that value individual diversity. The findings highlight the significance of holistic support from families, educational institutions, and society in maximizing the potential of ISN. This research offers theoretical and practical contributions by establishing an inclusive framework rooted in humanity and justice. The core essence is the paradigm shift from a deficit approach to valuing diversity. In conclusion, optimizing the potential of ISN requires synergy between theological and psychological perspectives, fostering social transformation towards a more inclusive society.